2022
DOI: 10.1021/acs.nanolett.2c01123
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Oxidative Microenvironment for In Vivo Synthesis of Subcellular Conductive Polymer Microesicles Enhances Nerve Reconstruction

Abstract: Conductive polymers (CPs) are promising biomaterials to address signal connection at biointerfaces for tissue regeneration. However, regulating material microstructure at the subcellular scale to provide a more seamless interface between conductive substrates and cells remains a great challenge. Here, we demonstrate that chemical factors and enzyme-carried subcellular structures at lesion site provide a natural bioreactor to selfassemble conductive microvesicles (CMVs) for improving bioelectrical signal recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This discovery has led to the creation of biohybrid plants with electronic roots , because of the in vivo enzymatic polymerization of conductive polymers. In further pursuits, Xu, Zhu and co-workers demonstrated the first in vivo enzymatic polymerization of polyaniline in rat models. In this study, aniline monomers were introduced in vivo at a crush injury site of the sciatic nerve in adult male Sprague–Dawley rats.…”
Section: Synthetic Coupling Strategiesmentioning
confidence: 99%
“…This discovery has led to the creation of biohybrid plants with electronic roots , because of the in vivo enzymatic polymerization of conductive polymers. In further pursuits, Xu, Zhu and co-workers demonstrated the first in vivo enzymatic polymerization of polyaniline in rat models. In this study, aniline monomers were introduced in vivo at a crush injury site of the sciatic nerve in adult male Sprague–Dawley rats.…”
Section: Synthetic Coupling Strategiesmentioning
confidence: 99%
“…These cells have a fundamental role in wound healing by their polarization [134,135] and are also critical elements in the inflammation phase. Generally, there are two types of polarized macrophages: M1, or classically activated macrophage, and M2, or activated macrophage [136], which play an essential role in repairing wounds. In normal wounds, M1 macrophages convert to M2 ones, but this process is impaired in diabetic wounds due to angiogenesis and collagen decreasing during wound closure [137].…”
Section: Macrophages Changes After Plasma Treatmentmentioning
confidence: 99%
“…A new approach to tackle this problem is by genetically programing specific cells within intact biological systems to build artificial structures with desired form and function in situ. It had previously been shown that conductive polymers can be directly synthesized on cells in living tissue with electrochemical polymerization 3 , or in organisms and tissues with native oxidative environments [4][5][6] or oxidative enzymes 7 . However, none of these approaches enabled the critical goal of cellular specificity.…”
Section: Mainmentioning
confidence: 99%